Do Black Holes Really Exist? - Rota, Luciano M.R. (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This article offers a brief critical research of the origins that gave rise to the theory of black holes and the ground on which it is based. The aim is to highlight some contradictions in the interior of the theory itself, which could seriously question their existence.